Characterizing the Mental Health Care of U.S. Cambodian Refugees - Wong, Eunice C (Psychiatr Serv, 2015)
OBJECTIVE: This study examined U.S. Cambodian refugees’ utilization of mental health services across various provider types, levels of minimally adequate care, and mode of communication with providers. METHODS: Face-to-face household interviews about past 12-month mental health service use were conducted as part of a study of a probability sample of Cambodian refugees. The analytic sample is restricted to the 227 respondents who met past 12-month criteria for posttraumatic stress disorder (PTSD) and/or major depressive disorder. RESULTS: 52% (N=127) of Cambodian refugees who met diagnostic criteria obtained mental health services in the past 12 months. Of those who obtained care, 80% (N=102) visited a psychiatrist and 52% (N=66) a general medical provider. Only 9% (N=11) had seen other mental health specialty providers. Virtually all respondents who had seen a psychiatrist (100%; N=102) or a general medical doctor (97%; N=64) had been prescribed a psychotropic medication. Approximately 45% (N=71) had received minimally adequate care. The large majority of Cambodian refugees relied on interpreters to communicate with providers. CONCLUSIONS: Cambodian refugee rates of mental health service utilization and minimally adequate care were comparable to individuals in the general U.S. population. In contrast to those of a nationally representative sample, Cambodian refugees obtained care almost entirely from psychiatrists and general medical doctors and nearly all were receiving pharmacotherapy. Given this pattern of utilization, and the persistently high levels of PTSD and depression found among Cambodian refugees, treatment improvements may require identification of creative approaches to delivering more evidence-based psychotherapy.